PENGARUH DANA PIHAK KETIGA, NON-PERFORMING LOAN DAN CAPITAL ADEQUACY RATIO TERHADAP RETURN ON ASSETS PADA SEKTOR PERBANKAN YANG TERDAFTARNDI BURSA EFEK INDONESIA - Hernadi Moorcy, Nadi; Nur Rizki, Novi (MEDIA RISET EKONOMI [MR.EKO], 2023)
The purpose of this study was to determine the Effect of Third Party Funds, Non-Performing Loans and Capital Adequacy Ratio on Return On Assets in the Banking Sector Listed on the Indonesia Stock Exchange. The data used are existing sources, both internal and external data and data can be accessed via the internet and information publications. The data used is the Financial Statements of Banking Companies for the period 2019 – 2022. The data analysis method uses multiple linear regression, the results of the analysis show that the variable Effect of Third Party Funds and Capital Adequacy Ratio has a significant effect on Return On Assets in the Banking Sector Listed on the Indonesia Stock Exchange, while the Non-Performing Loan variable has no significant effect on Return On Assets in the Banking Sector Listed on the Indonesia Stock Exchange